The Images of Aging in Al Arji’s Poetry - Lujain Bitar; Abdul Karim Yaqoub (دراسات في اللغة العربيّة وآدابها)
Thisresearch aims to unveil the nature of human spirit as reflected in the poems ofan Omayyad poet and describe the social changes that took place in the period,changes which had major influence on the poets’ ways of thinking during thatera. These changes have been revealed in the deep and sophisticated thinkingwhich have been featured clearly in the images for aging in Al Arji’s poetry.These images represent the voice of freedom and the metaphysic inspiration thatcan penetrate the unconscious sentiments of the human being and recreatehis/her picture of reality. Hence, these images are the most precise andreliable groundwork based on which one can formulate a novel picture of theOmayyad society. Poetic images of aging comprised a large bulk of the poems ofthis poet and therefore serve as an influential artistic tool in reshaping thefeatures of the portrait of the human being in the Omayyad society. Theseimages shows the emergence of story-telling in the Omayyad poetry which in turnadds distinctive artistic values and discloses the inner human characteristics.Moreover, these images provide us with different sentiments and sufferingswhich people have experienced during the Omayyad era.